Evaluation of comorbidity in patients with alcoholic cirrhosis of the liver associated with non-alcoholic fatty liver disease - N. R. Matkovska; N. H. Virstiuk; U. V. Balan (Zaporožskij Medicinskij Žurnal)
The aim of the study was to evaluate the concomitant pathology in patients with alcoholic cirrhosis of the liver associated with non-alcoholic fatty liver disease, depending on the compensation of the disease and patient's age.